Safety and efficacy of Lactobacillus buchneri DSM 29026 as a silage additive for all animal species. (29th June 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on Lactobacillus buchneri DSM 29026 when used as a technological additive to improve ensiling of forage. The additive is intended for use with all forages and for all animal species at a proposed minimum concentration of 1 × 10 8 colony‐forming units (CFU)/kg forage if used alone, or 5 × 10 7 CFU/kg forage if used in combination with other authorised microorganisms. The bacterial species L. buchneri is considered by the EFSA to be suitable for the qualified presumption of safety approach to safety assessment. As the identity of the strain has been clearly established and no acquired antimicrobial resistance determinants of concern were detected, the use of the strain as a silage additive is considered safe for livestock species, for consumers of products from animals fed the treated silage and for the environment. In the absence of data, the FEEDAP Panel cannot conclude on the potential of the additive to be a skin/eye irritant or skin sensitiser. Given the proteinaceous nature of the active agent, the additive should be considered a respiratory sensitiser. The FEEDAP Panel concluded that Lactobacillus buchneri DSM 29026 at a minimum concentration of 5 × 10 7 CFU/kg may improve the production of silage from easy and moderately difficult to ensile forage material.